(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To analyze factors related to rehabilitation treatment outcomes in patients with lumbar disc herniation at Functional Rehabilitation Department, Saint Paul General Hosptial in 2024. Subject and methods: A cross-sectional study analyzing factors associated with rehabilitation outcomes in patients with lumbar disc herniation. Result: Some factors related to rehabilitation treatment outcomes in patients with lumbar disc herniation include: mode of onset and circumstances of lumbar disc herniation occurrence; relationship between the severity of disc herniation and occupation; and association between gender and treatment outcomes prior to hospital discharge. Conclusion: Some factors related to rehabilitation treatment outcomes in patients with lumbar disc herniation include: mode of onset and circumstances of lumbar disc herniation occurrence, relationship between the severity of disc herniation and occupation and association between gender and treatment outcomes prior to hospital discharge.